Cardioprotective effects of curcumin against myocardial I/R injury: A systematic review and meta-analysis of preclinical and clinical studies - Li, Tianli; Jin, Jialin; Pu, Fenglan; Bai, Ying; Chen, Yajun; Li, Yan; Wang, Xian (Frontiers in Pharmacology, 2023)
Objective: Myocardial ischemia-reperfusion (I/R) injury is a complex clinical problem that often leads to further myocardial injury. Curcumin is the main component of turmeric, which has been proved to have many cardioprotective effects. However, the cardioprotective potential of curcumin remains unclear. The present systematic review and meta-analysis aimed to evaluate the clinical and preclinical (animal model) evidence regarding the effect of curcumin on myocardial I/R injury. Methods: Eight databases and three register systems were searched from inception to 1 November 2022. Data extraction, study quality assessment, data analyses were carried out strictly. Then a fixed or random-effects model was applied to analyze the outcomes. SYRCLE’s-RoB tool and RoB-2 tool was used to assess the methodological quality of the included studies. RevMan 5.4 software and stata 15.1 software were used for statistical analysis. Results: 24 animal studies, with a total of 503 animals, and four human studies, with a total of 435 patients, were included in this study. The meta-analysis of animal studies demonstrated that compared with the control group, curcumin significantly reduced myocardial infarction size (p < 0.00001), and improved the cardiac function indexes (LVEF, LVFS, LVEDd, and LVESd) (p < 0.01). In addition, the indexes of myocardial injury markers, myocardial oxidation, myocardial apoptosis, inflammation, and other mechanism indicators also showed the beneficial effect of curcumin (p < 0.05). In terms of clinical studies, curcumin reduced the incidence of cardiac dysfunction, myocardial infarction in the hospital and MACE in the short term, which might be related to its anti-inflammatory and anti-oxidative property. Dose-response meta-analysis predicted, 200 mg/kg/d bodyweight was the optimal dose of curcumin in the range of 10–200 mg/kg/d, which was safe and non-toxic according to the existing publications. Conclusion: Our study is the first meta-analysis that includes both preclinical and clinical researches. We suggested that curcumin might play a cardioprotective role in acute myocardial infarction in animal studies, mainly through anti-oxidative, anti-inflammatory, anti-apoptosis, and anti-fibrosis effects. In addition, from the clinical studies, we found that curcumin might need a longer course of treatment and a larger dose to protect the myocardium, and its efficacy is mainly reflected on reducing the incidence of myocardial infarction and MACE. Our finding provides some meaningful advice for the further research.